Pelatihan Mitigasi Bencana Menggunakan Tifa Syawat pada Masyarakat Suku Kokoda dalam Mewujudkan Kelurahan Klawalu Siaga Covid-19: Disaster Mitigation Training Using Tifa Syawat in the Kokoda Tribal Community in Realizing Klawalu Village Covid-19 Alert - Norma Norma; Radeny Ramdany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Covid-19 pandemic is a global disaster that is entering its second year; along with the development of the disease, there are changes in disease patterns, such as mutations that give birth to several new variants with higher infectious power. In Sorong City, the number of positive cases was 6,145 cases, the number of deaths was 93 deaths, and the cure rate was 6,030 people. Klawalu Village, one of the villages in the East Sorong district, is a Community Service (PkM) partner and has been actively involved in preventing and handling Covid-19 cases. However, it is still found in public places such as markets, motorcycle taxi bases, and on the outskirts of the road; some people need to obey health protocols such as not wearing masks and crowding. This condition illustrates that education and appeals are not enough to change society to behave healthily. It is necessary to provide skills based on local wisdom in preventing and handling Covid-19 so that the community can independently recognize risk factors, prevent, maintain, maintain, and even improve their health degree. The results of the PkM activity showed that after being given Covid-19 education, as many as 32 (94.1%) participants had good knowledge, as many as 32 (94.1%) participants were skilled in mitigating the Covid-19 disaster, the formation of Covid-19 Alert cadres and the Covid-19 Alert Post Klawalu Village.